P201 Assessment of factors associated with cumulative bowel damage in surgically naïve patients using Lemann index and global MaRIA index in Crohn's disease. (30th January 2023) - Domislović, V; Hrabric Sonje, K; Brinar, M; Cukovic-Cavka, S; Turk, N; Grgic, D; Barisic, A; Jelakovic, M; Prutki, M; Krznaric, Z
Abstract: Background: The Lémann index (LI) is a unique tool that measures cumulative bowel damage in Crohn's disease (CD) and is composed of surgical procedures and severity and extent of bowel lesions according to endoscopy and MR enterography (MRE). Since there is a significant contribution of previous surgery in LI calculation, our aim of this study is to investigate factors associated with cumulative bowel damage using LI in both total population and surgically naïve patients. Methods: In this cross-sectional study, LI was calculated evaluating 20 small bowel, 7 large bowel and 3 upper GI segments. For each segment bowel resections, inflammatory, stricturing or penetrating lesions were considered using MRE and upper and lower endoscopy. Global MaRIA (gMaRIA) index was calculated using following parameters on 6 bowel segments on MRE: bowel wall thickness, ulcers, edema, and relative contrast enhancement. Longstanding disease was ≥10-year duration. Disease activity was defined as CRP>5 or HBI≥5. Extent and disease behavior were assessed using Montreal classification. Multivariate logistic regression adjusted for confounders was performed (age, gender, BMI, smoking status, CRP, disease behavior and extension, biological therapy, gMaRIA score, and HBI). Results: This study included 320 CD patients [age 36 (24-46), 54.6% males, disease duration 7.2 (1-14) years, BMI 21.3 (17.4-24.8) kg/m2]. There were 142 (44.4%) surgically naïve and 128 (40%) patients with longstanding disease. In total population, higher LI values were observed among those with longstanding disease (10.31 vs 5.35 years, p<0.001), patients treated with biological therapy (9.7 vs. 6.4, p=0.005) and prior surgery (11.81 vs. 1.62, p<0.005). There was no difference in LI according to activity (p=0.921) and smoking status (p=0.336). Multivariate analysis on total population revealed independent predictors of elevated LI which were BMI (β=-0.268, p<0.02), disease duration (β=0.120, p=0.041) and prior surgery (β=5.42, p<0.001). Hence, separate multivariate analysis was performed on surgically naïve which revealed following predictors of LI (other than surgery): current smoking (β=1.14, p=0.010), perianal disease (β=1.39, p=0.02) and gMaRIA score (β=0.093, p<0.001). Conclusion: Positive predictors of cumulative bowel damage in surgically naïve patients were smoking, perianal disease, and radiological activity (gMaRIA), while in total population longer disease duration, BMI and prior surgery. There are several important contributing variables on cumulative bowel damage which were revealed after removing previously operated patients, which would otherwise remain unrecognized. This risk factors in CD could stratify patients at high risk for complicated course of disease.